Comparison between the effects of diallyl tetrasulfide on human retina pigment epithelial cells (ARPE-19) and HCT116 cells - Saidu, Nathaniel Edward Bennett; Abu Asali, Imad; Czepukojc, Brigitte; Seitz, Berthold; Jacob, Claus; Montenarh, Mathias (Biochimica et biophysica acta, 2013)
Diallyl mono- and polysulfanes from garlic are known to induce an adaptive cell response and the formation of antioxidants in cancer cells. In the case of a severe ER stress and a failure in the response, cancer cells eventually go into apoptosis. Only little is known about the response of normal cells upon treatment. Normal ARPE-19 cells were treated with diallyl tetrasulfide to study their cellular response and the results were compared with those of HCT116 cancer cells. Cell viability was checked by an MTT assay and cytofluorimetry. The formation of superoxide radicals, H2O2 and thiols were determined and proteins involved in the ER stress response were also detected by Western blot analysis. We found that diallyl tetrasulfide induced reactive oxygen species (ROS) in normal cells similar to cancer cells in a time (0 to 60min) and dose dependent manner (0 to 50μM). The level of heme oxigenase-1 (HO-1) was up-regulated in both cell types. Initially, we found a decrease in the total thiol level in both cell types but in contrast to cancer cells, normal cells recovered from the decrease in the total thiol concentration within 60min of treatment. The recovery of the thiol concentration in normal cells treated with diallyl tetrasulfide seems to be responsible for the failure to induce the ER stress signalling pathway and finally apoptosis in normal cells. The difference in the recovery of the thiol status might be an explanation for the anti-carcinogenic effects of garlic compounds. [Display omitted] •DATTS treatment leads to the induction of ROS and reduction of thiols.•In contrast to cancer cells, reduction of thiols in normal cells is transient.•DATTS treatment of cancer cells leads to ER stress signalling and apoptosis.•In normal cells there is no ER stress signalling and no apoptosis.